The political and economic integration between Latin America and the European Union: at what point are we in the case of the Andean Community? - García Álvarez, Santiago (2016)
This article presents a brief analysis of the present situation of the negotiations to establish an Association Agreement between the European Union and the Andean Community, using as a starting point the results of the 1VEuropean Union-Latin America and Caribbean Summit carried out in Vienna in 2006. Such negotiations also take into account the latest decisions of the Andean Presidential Council, in which can be found some defining elements of what could be Andean-European integration, an integration thats without a doubt, constitutes a priority for the Andean countries as well as for the rest of Latin America.